2014
DOI: 10.1128/cvi.00715-13
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Peripheral Blood Coxiella burnetii DNA Load, Interleukin-6 Levels, and C-Reactive Protein Levels in Patients with Acute Q Fever

Abstract: e From 2007 to 2010, the Netherlands experienced the largest reported Q fever outbreak, with >4,000 notified cases. We showed previously that C-reactive protein is the only traditional infection marker reflecting disease activity in acute Q fever. Interleukin-6 is the principal inducer of C-reactive protein. We questioned whether increased C-reactive protein levels in acute Q fever patients coincide with increased interleukin-6 levels and if these levels correlate with the Coxiella burnetii DNA load in serum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Of these markers, CRP and IL-6 were strongly increased in the acute Q fever group and to a lesser extent in the vascular chronic Q fever group compared to the past resolved Q fever group. Recent findings obtained in acute Q fever patients from the same outbreak also showed correlated responses between these two acute-phase response markers (20). We also show here that a set of CC-type chemokines (MIP1␣, RANTES, and eotaxin-1) shows downregulation in acute Q fever patients and a heterogeneous response in the group of vascular chronic Q fever patients.…”
Section: Discussionsupporting
confidence: 48%
“…Of these markers, CRP and IL-6 were strongly increased in the acute Q fever group and to a lesser extent in the vascular chronic Q fever group compared to the past resolved Q fever group. Recent findings obtained in acute Q fever patients from the same outbreak also showed correlated responses between these two acute-phase response markers (20). We also show here that a set of CC-type chemokines (MIP1␣, RANTES, and eotaxin-1) shows downregulation in acute Q fever patients and a heterogeneous response in the group of vascular chronic Q fever patients.…”
Section: Discussionsupporting
confidence: 48%
“…The NCSI has been used in previous studies assessing health status after Q fever infection [5, 6, 1113]. It is based on an empirical definition of health status, covering ‘physiological functioning’, ‘symptoms’, ‘functional impairment in daily life’, and ‘quality of life’ as main domains.…”
Section: Methodsmentioning
confidence: 99%
“…Of the 28 articles that contained information on aetiology, 18 were classified in the main table aetiology ( S4 Table ) [ 18 21 , 36 38 , 45 51 , 54 , 55 , 60 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…burnetii antibodies disappeared [ 55 ]. In acute Q-fever IL-6 and CRP seemed predictive of more severe disease, but no support was found that these were associated with prolonged fatigue [ 63 ]. Markers of inflammation and pro-inflammatory cytokine concentrations did not remain altered in patients with post-infective fatigue [ 12 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation